Fat-free milk as a therapeutic approach for constipation and the effect on serum motilin and ghrelin levels - Aydin, Suleyman; Donder, Emir; Akin, Okhan K.; Sahpaz, Fatih; Kendir, Yalcin; Alnema, Manar M. (Elsevier Science Inc, 2010)
Objective: This study explores the effects of fat-free milk supplementation on individuals with chronic constipation with regard to levels of motilin and acylated and des-acylated ghrelin (which affect intestinal motility) and compares them with data from control subjects given whole milk supplementation. Methods: The investigation was designed according to the constipation severity test of individuals whose ages and body mass indexes were comparable. Individuals with mild constipation (n = 10) were supplemented with 400 mL of fat-free milk daily; moderate constipation cases (n = 10) were supplemented with 600 mL, and severe constipation cases (n = 10) were supplemented with 800 mL of fat-free milk daily. Healthy control subjects were administered 400 mL of fat-free milk (group 1), which was followed a month later by administration of 400 mL of whole milk for 3 days (group 2). Blood samples were collected from the subjects before and after milk supplementation for hormone analyses. Motilin and acylated and des-acylated ghrelin were quantified with ELISA assay. Results: Supplementation of fat-free milk significantly increased levels of circulating motilin and ghrelin in all groups, including the control subjects, but whole milk supplementation led to a decrease in these hormone levels in the control subjects. Conclusion: Drinking fat-free milk might be a new way of solving constipation. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Constipation; Motilin; Ghrelin; Milk